Haemorrhage after liver biopsy in a dog with portosystemic shunt. Issue 1 (13th August 2014) - Katić, Nikola; Katić, Christina; Reifinger, Martin; Dupré, Gilles
Abstract : A 5‐year‐old intact female Chihuahua was transferred to our hospital for attenuation of a portosystemic shunt. The attenuation was done by means of cellophane banding and a routine liver biopsy was taken. Postoperatively, the dog developed haemoabdomen and the haematocrit dropped to 11 per cent. Relaparotomy revealed an acute haemorrhage from the biopsy site and partial liver lobectomy was performed to control bleeding. Despite all attempts at treatment, the dog developed serious metabolic and respiratory derangements and eventually died after an episode of respiratory arrest. With this report, the authors want to raise awareness of this potentially fatal complication and motivate the readers to weigh the benefit of additional information against the risk a 'simple' liver biopsy could entail in animals undergoing portosystemic shunt attenuation.